Nursing staffs self-perceived outcome from a rehabilitation 24/7 educational programme - a mixed-methods study in stroke care - M. I. Loft; B. A. Esbensen; K. Kirk; L. Pedersen; B. Martinsen; H. Iversen; L. L. Mathiesen; I. Poulsen (BMC, 2018)
Abstract Background During the past two decades, attempts have been made to describe nurses' contributions to the rehabilitation of inpatients following stroke. There is currently a lack of interventions that integrate the diversity of nurses' role and functions in stroke rehabilitation and explore their effect on patient outcomes. Using a systematic evidence- and theory-based design, we developed an educational programme, Rehabilitation 24/7, for nursing staff working in stroke rehabilitation aiming at two target behaviours; working systematically with a rehabilitative approach in all aspects of patient care and working deliberately and systematically with patients' goals. The aim of this study was to assess nursing staff members' self-perceived outcome related to their capability, opportunity and motivation to work with a rehabilitative approach after participating in the stroke Rehabilitation 24/7 educational programme. Methods A convergent mixed-method design was applied consisting of a survey and semi-structured interviews. Data collection was undertaken between February and June 2016. Data from the questionnaires (N = 33) distributed before and after the intervention were analysed using descriptive statistics and Wilcoxon sign rank test. The interviews (N = 10) were analysed using deductive content analysis. After analysing questionnaires and interviews separately, the results were merged in a side by side comparison presented in the discussion. Results The results from both the quantitative and qualitative analyses indicate that the educational programme shaped the target behaviours that we aimed to change by addressing the nursing staff's capability, opportunity and motivation and hence could strengthen the nursing staff's contribution to inpatient stroke rehabilitation. A number of behaviours changed significantly, and the qualitative results indicated that the staff experienced increased focus on their role and functions in rehabilitation practice. Conclusion Our study provides an understanding of the outcome of the Rehabilitation 24/7 educational programme on nursing staff's behaviours. A mixed-methods approach provided extended knowledge of the changes in the nursing staff members' self-percived behaviours after the intervention. These changes suggest that educating the nursing staff on rehabilitation using the Rehabilitation 24/7 programme strengthened their knowledge and beliefs about rehabilitation, goal-setting as well as their role and functions.